Current classification of the Bacillus pumilus group species, the rubber-pathogenic bacteria causing trunk Bulges disease in Malaysia as assessed by MLSA and multi rep-PCR approaches - Azman Husni, Ainur Ainiah; Ismail, Siti Izera; Md Jaafar @ Ahmad Jaafar, Noraini; Zulperi, Dzarifah (Wiley-Blackwell Publishing, 2021)
Bacillus pumilus is the causal agent of trunk bulges disease affecting rubber and rubberwood quality and yield production. In this study, B. pumilus and other closely related species were included in B. pumilus group, as they shared over 99.5% similarity from 16S rRNA analysis. Multilocus sequence analysis (MLSA) of five housekeeping genes and repetitive elements-based polymerase chain reaction (rep-PCR) using REP, ERIC, and BOX primers conducted to analyze the diversity and systematic relationships of 20 isolates of B. pumilus group from four rubber tree plantations in Peninsular Malaysia (Serdang, Tanah Merah, Baling, and Rawang). Multi rep-PCR results revealed the genetic profiling among the B. pumilus group isolates, while MLSA results showed 98-100% similarity across the 20 isolates of B. pumilus group species. These 20 isolates, formerly established as B. pumilus, were found not to be grouped with B. pumilus. However, being distributed within distinctive groups of the B. pumilus group comprising of two clusters, A and B. Cluster A contained of 17 isolates close to B. altitudinis, whereas Cluster B consisted of three isolates attributed to B. safensis. This is the first MLSA and rep-PCR study on B. pumilus group, which provides an in-depth understanding of the diversity of these rubber-pathogenic isolates in Malaysia.